Brief Bubble and Intermittent Surface Oxygenation Is a Simple and Effective Alternative for Membrane Oxygenation During Hypothermic Machine Perfusion in Kidneys. Issue 7 (July 2020) - Darius, Tom; Vergauwen, Martial; Mueller, Matteo; Aydin, Selda; Dutkowski, Philipp; Gianello, Pierre; Mourad, Michel
Abstract : Background: The aim of this feasibility study was to determine an alternative oxygenation technique (easy, cheap, and compatible with air transport) for membrane oxygenation during hypothermic machine perfusion (HMP) to improve early graft function in a porcine ischemia-reperfusion autotransplant model. Methods: The left kidney of a ±40- kg pig was exposed to 30 minutes of warm ischemia before 22 hours of preservation and autotransplantation. In the experimental group, oxygenation of the perfusate during HMP was obtained by direct bubble and 30-minute surface oxygenation at start and 1-hour end ischemic (n = 4) and outcome measures compared with historical HMP without active oxygenation (n = 6), 22-hour continuous oxygenated HMP (HMPO2 ) (n = 8), and 2-hour HMPO2 + 20-hour HMP (n = 6) using membrane oxygenation in both historical oxygenated control groups. Results: Brief bubble and 30-minute surface oxygenation of the perfusate effectively maintained supraphysiological PO2 levels during the first 2 hours of HMP with improved flow dynamics. Although the metabolic profile of the perfusate (ie, flavin mononucleotide) and tissue (ie, glutamate, ATP) after brief O2 uploading at the start of HMP seemed to be slightly better with the use of a membrane oxygenator compared with bubble and interrupted surface oxygenation, both techniques yielded similar, superior early graft function when compared with HMP without active oxygenation. Conclusions: The data presented in this feasibility study support the conclusion that brief bubble and intermittent surface oxygenation could be an alternative oxygenation technique during HMP to achieve an improved kidney graft function compared with HMP without active oxygenation and similar functional outcome when compared with membrane HMPO2 .